2013
DOI: 10.1021/ja4001823
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fungal Iterative Polyketide Synthase Functions Using Partially Assembled Intermediates

Abstract: Iterative polyketide synthases (PKS) are large multifunctional enzymes that resemble eukaryotic fatty acid synthases, but can make highly functionalized secondary metabolites using complex and unresolved programming rules. During biosynthesis of the kinase inhibitor hypothemycin by Hypomyces subiculosus, a highly-reducing iterative PKS, Hpm8, cooperates with a non-reducing iterative PKS, Hpm3, to construct the advanced intermediate dehydrozearalenol (DHZ). The identity of putative intermediates in the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…1A). This type of divergence in ␤-keto group modification is not known for bacterial iterative PKS systems and has some precedents only in fungal type I PKS systems (10,11). An iterative PKS system that incorporates methylmalonyl-CoA has not been reported, whereas the ability of FAS to incorporate methylmalonyl-CoA has been observed for mycocerosic acid synthase (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). This type of divergence in ␤-keto group modification is not known for bacterial iterative PKS systems and has some precedents only in fungal type I PKS systems (10,11). An iterative PKS system that incorporates methylmalonyl-CoA has not been reported, whereas the ability of FAS to incorporate methylmalonyl-CoA has been observed for mycocerosic acid synthase (23).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal type I PKSs are iterative, but their products are not limited to aromatic compounds (9). The highly reducing, iterative fungal PKSs synthesize complex polyketide structures by selectively employing post-condensational modification activities in a highly programmed manner (10,11). In these fungal PKSs, the selective usage of the modification activities in each condensation step generates complex polyketide structures.…”
Section: Galbonolide (Gal)mentioning
confidence: 99%
“…Zhou et al and Gao et al both fed large acyl SNAC (N-acetylcysteamine thioester) substrates to fungal iPKSs expressed or purified from BJ5464-NpgA (Zhou et al, 2010; Gao et al, 2013). Both groups were able to produce unnatural analogs of the relevant natural product.…”
Section: Combinatorial Biosynthesis Of Fungal Pkss In S Cerevisiaementioning
confidence: 99%
“…Both groups were able to produce unnatural analogs of the relevant natural product. Gao et al found that the efficiency of incorporation of the unnatural precursor analogs depended on the nature of the structural changes between these analogs and the natural precursors (Gao et al, 2013). …”
Section: Combinatorial Biosynthesis Of Fungal Pkss In S Cerevisiaementioning
confidence: 99%
“…Further building on the impressive body of work compiled by the Tang and Vederas laboratories on fungal iPKS systems (9,16,17), in the present study, Xu et al take a significant step forward and explore how structural diversity for BDLs can be generated by pairwise combination of hrPKS and nrPKS modules derived from four different BDL biosynthetic gene clusters. In addition to CcRad and AtCur gene loci, they further expand their approach to include the newly discovered lasiodiplodin and resorcylide biosynthetic iPKSs from Lasiodiplodia theobromae (LtLas) and Acremonium zeae (AzRes), respectively (11), to provide 16 possible hrPKS-nrPKS combinations.…”
mentioning
confidence: 95%